THE ROLE OF INVENTORY IN CIRENG AND CIMOL NELLA'S BUSINESS DEVELOPMENT IN THE COVID-19 PANDEMIC PHASE - Susanto, Resi Juariah (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2023)
This community service was carried out with the aim of improving the inventory system method for Cireng and Cimol Nella SMEs. Where at this time the service also provided assistance and carried out directly or practiced in calculating inventory using the EOQ method so that it was precise and no raw materials were wasted so as not to cause harm to the cireng and cimol nella business owners. The problem that is often faced by Cireng and Cimol Nella MSME actors is the inaccuracy of ordering raw materials so that orders are made continuously, in the pandemic era, entrepreneurs want effective ordering of raw materials so they don't often meet with suppliers so that when ordering raw materials they can be stored for not too long to avoid damaged products and make product quality less good too. The method used is the EOQ (Economic Order Quantity) method with a yield of 885 kg for each order with a total order of 3 orders per year. The output targets to be achieved are in the form of publication in journals and increased understanding and skills of business actors. Key words: abstract, italic, mathematical equation